Family law. Vol. 2, Marriage, divorce and matrimonial litigation - Flavia (New Delhi ; Oxford : Oxford University Press, 2012)
This study on family law in India combines women's rights with legal theory, and uses case laws extensively. It discusses the concepts of justice, law, and gender, examines various personal laws related to marriage, property rights, succession, and divorce.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Domestic relations -- India; Women's rights -- India; Constitutional law -- India; Citizenship -- India